2013
DOI: 10.5539/jas.v5n9p222
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Selected Seed Genotypes of Prunus armeniaca L. for Harvesting Seeds for the Production of Generative Rootstocks for Apricot Cultivars

Abstract: In 2008-2011, at the Research Institute of Horticulture in Skierniewice, Poland seven genotypes of Prunus armeniaca L., designated MN-1, MN-2, MN-4, MN-6, MN-46, MN-53 and MN-59, were evaluated for use as trees to provide seeds for the production of generative rootstocks for apricot cultivars. The study was conducted on trees growing in the Experimental Orchard in Dąbrowice (central Poland). The best as seed trees proved to be genotypes MN-4 and MN-46. Their flower buds are resistant to frost, the flowers are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In the months of July and August of 2010 and 2012, higher temperatures were recorded compared with those in 2009 and 2011, which contributed to the fruit development and seed maturation. Variations in germination capacities depending on the growing season were also reported in the sweet cherry (Suszka 1976), apple (Lewandowski, Żurawicz 2009), and apricot (Szymajda et al 2013b). The results of our four-year study have shown that the seeds of the tested genotypes have significantly higher germination capacities compared with those of the control cvs Mandżurska and Siberian C. Among the tested genotypes, the seeds with the highest germination capacities were produced by the trees of BN-3, BN-4 and BN-8.…”
Section: Resultsmentioning
confidence: 78%
“…In the months of July and August of 2010 and 2012, higher temperatures were recorded compared with those in 2009 and 2011, which contributed to the fruit development and seed maturation. Variations in germination capacities depending on the growing season were also reported in the sweet cherry (Suszka 1976), apple (Lewandowski, Żurawicz 2009), and apricot (Szymajda et al 2013b). The results of our four-year study have shown that the seeds of the tested genotypes have significantly higher germination capacities compared with those of the control cvs Mandżurska and Siberian C. Among the tested genotypes, the seeds with the highest germination capacities were produced by the trees of BN-3, BN-4 and BN-8.…”
Section: Resultsmentioning
confidence: 78%
“…Apricot seeds require cold stratification to break dormancy. For this, it is necessary to keep the apricot seeds at 4-7 ºC degree for 90-105 days (Fadl et al 1978;Polat 2007;Szymajda et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is a well-known fact that the deep dormancy of Prunus seeds is broken during their post-harvest maturation while being subjected to stratification (Suszka, 1967;Mehanna & Martin, 1985;Martínez-Gómez & Dicenta, 2001;Jensen & Kristiansen, 2009;Seliga & Żurawicz, 2011;Szymajda, et al, 2011;Szymajda, et al, 2013;Szymajda & Żurawicz, 2014), under the influence of low temperature, causing the decomposition of germination inhibitors (Chen et al, 2007). It is often the case, however, that even after long-lasting, stratification, not all of the stratified seeds germinate.…”
Section: Introductionmentioning
confidence: 99%